The Effectiveness of Group Guidance Using the Problem Solving Method in Enhancing Students' Career Understanding - Putri, Rolin; Fitria Kasih; Rici Kardo (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the phenomenon of low levels of career understanding of students. The purpose of this study is to describe the description of students' career understanding before being given group guidance services using the problem solving method. The description of students' career understanding after being given group guidance services using the problem solving method. The effectiveness of group guidance using the problem solving method in improving students' career understanding. The type of research used in this study is an experimental method with a One Group Pre-test-Post-test Design research design, while the sampling technique is carried out using a purposive sampling technique. The instrument used is a questionnaire, while for data analysis using t-test analysis. The results of this study given group guidance services using the problem solving method are in the low category with a percentage of 40%. The description of students' career understanding after being given group guidance services using the problem solving method is in the high category with a percentage of 90%. It can be seen that the average career understanding before receiving group guidance services using the problem solving method is 122 and the average level of career understanding after receiving group guidance services using the problem solving method is 182. This means that group guidance services using the problem solving method are effective in increasing the career understanding of class XI students in phase F6 at SMA Negeri 7 Sijunjung. The results of this study are recommended to guidance and counseling teachers to be able to integrate this service in a structured manner in guidance and counseling services, especially by using group guidance.